Recycling of Multilayer Polymeric Barrier Films: an Overview of Recent Pioneering Works and Main Challenges - Hissein Bechibo Adam; Mohamed Yousfi; Abderrahim Maazouz; Khalid Lamnawar (Macromolecular Materials and Engineering)
Abstract Multilayer barrier flexible polymer films are gaining attention for their lightness and versatility, representing over 17% of global plastic packaging production, primarily in the food sector. However, their complex chemical composition and strong interlayer adhesion—due to the presence of tie layers pose significant recycling challenges. This review explores waste management technologies for these complex films, including physical recycling (mechanical recycling, delamination, and selective dissolution‐precipitation) and chemical recycling (pyrolysis, gasification, and depolymerization). Among them, mechanical recycling is the least energy‐intensive and most environmentally friendly but is hindered by polymer degradation. Delamination, the least impactful solvent‐based method, offers advantages, while selective dissolution‐precipitation achieves high polymer purity but has a substantial environmental footprint due to excessive solvent use. Chemical recycling, though highly energy‐intensive, produces derivatives with purity comparable to virgin materials. Therefore, the recent insights into each recycling process and their main scientific and technological challenges are summarized and discussed. Furthermore, life cycle assessment (LCA) studies on multilayer film waste management are reviewed. One proposed eco‐design strategy involves transitioning from multi‐material to mono‐material multilayer films, offering a promising path toward sustainable management.